Formation of Patience and Trust Character Through the Learning Theme of the Hijrah Story of the Prophet Muhammad SAW in Grade 4b Students of SD Negeri 22 Baubau - Haziz, Haziz; Basri, Basri; Madi, Madi (Journal of English Language and Education, 2026)
This studi aims to examine teh process of developing the characters of patience and trustworthiness through the learning theme of the Hijrah story of Prophet Muhammad among fourth-grade students at SD Negeri 22 Baubau. This study employs a qualitative approach to understand students’ character development within the context of Islamic exemplary values. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The findings indicate that learning activities based on the Hijrah story of Prophet Muhammad (peace be upon him) contribute to fostering the characters of patience and trustworthiness among students, although the level of understanding and application varies among them. Some students have demonstrated patient and trustworthy behavior in their daily activities, while others still require continuous habituation and guidance. This study highlights the importance of teachers’ role modeling and habituation processes in strengthening the internalization of the values of patience and trustworthiness. Therefore, it can be concluded that exemplary story-based learning plays an important role in shaping the characters of patience and trustworthiness in elementary school students.